Sleep quality in men with androgenetic alopecia - Liamsombut S. (2023)
Purpose: Sleep disturbances affect human health and contribute to several comorbidities. In men, androgenetic alopecia (AGA) is a common, non-scarring form of hair loss that affects a patient’s self-esteem. There are limited data regarding the association between poor sleep quality and male AGA. We aimed to compare the prevalence of sleep abnormalities between male patients with AGA and controls to identify an association between the two conditions. Methods: A case–control study on patients with AGA and age-matched controls was conducted. Participants completed a standardized questionnaire that contained self-evaluated sleep measures, including Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale, and STOP-BANG questionnaire. Patients with AGA were classified into mild, moderate, and severe subgroups according to the Hamilton-Norwood classification for stratified analyses. Data between groups and among subgroups were compared. Results: Of 446 male participants, 223 (50%) were in the AGA group, and the remainder (50%) were in the control group. Multivariable logistic regression analysis revealed that hypertension (odds ratio [OR] = 1.90, 95% confidence interval [CI] = 1.16–3.11, p = 0.011) and STOP-BANG score ≥ 5 (OR = 2.05, 95%CI = 1.15–3.66, p = 0.015) were associated with AGA. For subgroup analyses, ordinal logistic regression model showed a significant association between severe AGA and three sleep profiles, namely total sleep time ≤ 6 h (OR = 2.16, 95%CI = 1.02–4.57, p = 0.044), PSQI > 5 (OR = 3.72, 95%CI = 1.42–9.72, p = 0.008), and STOP-BANG score ≥ 5 (OR = 3.01, 95%CI = 1.11–8.13, p = 0.030). Conclusion: Our findings revealed an association between sleep disturbances and AGA, which may help guide appropriate management in these patients.